Cover Picture: Overcoming Bottlenecks of Enzymatic Biofuel Cell Cathodes: Crude Fungal Culture Supernatant Can Help to Extend Lifetime and Reduce Cost (ChemSusChem 7/2013). Issue 7 (4th July 2013) - Sané, Sabine; Jolivalt, Claude; Mittler, Gerhard; Nielsen, Peter J.; Rubenwolf, Stefanie; Zengerle, Roland; Kerzenmacher, Sven
<x xml:space="preserve">Abstract</x> The cover image shows the wood‐degrading fungus Trametes versicolor that naturally secretes the redox‐enzyme laccase. Without further enzyme purification, the laccase‐containing culture supernatant can be supplied to an enzymatic biofuel cell cathode, at which it catalyzes the oxygen reduction reaction. Kerzenmacher et al. show in their manuscript on page 1209 that the enzymes lose catalytic activity with time; for this reason, fresh culture supernatant is regularly resupplied to the electrode to replace the deactivated laccase enzymes. In this way, a comparably simple and cost‐efficient enzymatic biofuel cell cathode with an extended lifetime can be established.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>